1970
DOI: 10.1002/j.2050-0416.1970.tb03260.x
|View full text |Cite
|
Sign up to set email alerts
|

FACTORS AFFECTING THE PRODUCTION OF Α-Amylase IN BARLEY GRAINS

Abstract: The production of α‐amylase by the endosperm of barley varieties, both commercial and non‐commercial, in normal germination and after incubation with gibberellic acid, has been measured. The level of activities produced differed considerably between varieties. All varieties tested produced considerably more enzyme when supplied with a source of exogenous gibberellic acid than under normal germination. In general the differences between varieties were less in the de‐embryonated treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The common result is that in germinating cereals there is either tio effect at all (e.g. Khan andFaust 1967, Murata et al 1968) or that the effect is relatively trivial (Atanda andMiflin 1970, R. L. Jones andArmstrong 1971). R. L. Jones and Armstrong (1971), who showed that added gibberellin penetrated the seed, concluded that "seeds allowed to germitiate in solutions of GAj of 0.5 and 50 |iM" (concentrations 100 and 10,000 x the endogenous) "did not accutnulate significatitly higher levels of a-amylase than those on water alone".…”
Section: Failure To Relate Endogenous Gibberellin Concentrations Withmentioning
confidence: 99%
“…The common result is that in germinating cereals there is either tio effect at all (e.g. Khan andFaust 1967, Murata et al 1968) or that the effect is relatively trivial (Atanda andMiflin 1970, R. L. Jones andArmstrong 1971). R. L. Jones and Armstrong (1971), who showed that added gibberellin penetrated the seed, concluded that "seeds allowed to germitiate in solutions of GAj of 0.5 and 50 |iM" (concentrations 100 and 10,000 x the endogenous) "did not accutnulate significatitly higher levels of a-amylase than those on water alone".…”
Section: Failure To Relate Endogenous Gibberellin Concentrations Withmentioning
confidence: 99%
“…Further, MacGregor et al reported a slight increase in the peak gelatinisation temperature from barley and malt. Up to 10% of barley starch is degraded by enzymes during malting into oligosaccharides and sugars . The changes to barley starch structure during malting result in different values of GT.…”
Section: Introductionmentioning
confidence: 99%